VALIDITAS E-MODUL BERBASIS WEBSITE PADA MATA KULIAH PADUAN SUARA: STUDI PENELITIAN PENGEMBANGAN - Sagala, Mastri Dihita (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
This study aims to reveal the validity of a website-based e-module used for choir learning for students of the Performing Arts Education Study Program at Tanjungpura University. The making is based on the fact in class that students often do not bring sheet music as a source of choir learning. The song sheet music is then packaged through the Sibelius Ultimate and Publuu applications into the LMS (Learning Management System) website. This research uses the R&D (Research and Development) research method. The stages consist of define, design, development and dissemination. Data collection techniques using interviews and distributing questionnaires. The research instruments used were material expert validators, media experts and users by distributing questionnaires. Data analysis using Likert scale technique obtained results of 92% by media experts, 99% by material experts and 76.67% by users so that this e-module is valid for use. The results of this study have implications for website-based e-modules that can be utilized by students as a source of independent choir learning. This e-module has implications for improving students' ability to read block notation through independent exercises that are carried out easily and flexibly.